Método da sísmica de reflexão aplicado à identificação dos recursos minerais marinhos na Plataforma Continental: uma pesquisa bibliográfica - SANTOS, Erlane Pereira dos (2020)
The seismic reflection method (SR) is based on the propagation of elastic waves into earth’s subsurface. The phenomenon of reflection is produced by the contrast impedance between two medium that depends on density and velocity propagation of waves into geological medium. The sediments density, in turn, depends on the mineralogy, porosity and water content, these parameters are drivers the sediments impedance. In investigation of sediments superficial layers, velocity propagation values are assumed as about 1.450 e 1.550 m/s into water, and 1.400 e 1.700 m/s into sediments shallow unconsolitated. The presence of gas in the sediments can make this value decreases to about 800 m/s. The SR is commonly used for marine mineral exploration for reporting the submerged substrate with good level of resolution. Few studies about the SR application in the marine mineral research in the continental shelves are available. Thus, justified this bibliographic research which investigated: the historical aspects of seismic methods and mineral prospection, the geology of marine mineral deposits, the seismic sources and frequency, and the informations extracted from the SR. Are exhibited the particularities of SR with several seismic sources types (airgun, sparker, boomer, system transducer and chirp) and the frequency of investigation to high resolution surveys. For the litoclastic and bioclastic granular, placers and phosphorite located in the seafloo r are used frequency < 2 kHz. The main sources suitable for this object are boomer and chirp. For studies of the fine sediments deposits and the object is resolution, should be used frequencies between 2 and 30 kHz. System transducers and chirp are used to this finality. In relation to the processing, this is not so well established as that used in conventional seismic. Information covers the identification of paleoenviroments (paleobeach and paleochannel), types of sediments, faults, paleoenvironmental reconstruction from the change of sea level and sismostratigraphy, thickness of layers, acoustic basement and 3D mapping of features and layers of interest. In the paleoenvironments may occur accumulations of heavy minerals and may indicate placers. The sediments can be classified from your echo character. The discontinuous echos and with little penetration, these are associated to coarse sediments (sand and gravel). While continuous echos with good penetration are associated to mud sediments, that can contain gas producing acoustic anomalies of strong reflectivity. The sediments with phosphorites concretions produce echo character with hyperbole small-scale. Faults may assist in capturing placers and their identification is made through evidence as diffractions and reflections from discontinuities. The Sismostratigraphy provides informations about change on sea level, determinant factor to minerals deposits accumulation. The thickness of layers is obtained from times registered in the SR. The acoustic basement can reveal traps for placers. The 3D mapping of features and layers helps in evaluation and quantification of minerals field.